2017
DOI: 10.1021/acssuschemeng.7b01684
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanism on Selective, Rapid, and Superior Adsorption of Congo Red by Reusable Mesoporous α-Fe2O3 Nanorods

Abstract: A large scale synthesis of mesoporous hematite (α-Fe2O3) nanorods with a high surface area of 98 m2/g and an average pore size of ∼26 nm was used for adsorption studies for pollutant dye removal. The nanorods exhibited rapid, superior, and selective adsorption efficiency toward Congo red, an organic dye present in wastewater. Highly selective adsorption capability of the mesoporous α-Fe2O3 nanorods has been attributed to the presence of abundant surface active sites with porous networks which make it highly wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…If the intercept (c) in the internal diffusion model is 0, it means that the internal diffusion is the only speed control step. 20 Obviously, it can be seen that c is not zero from Table S2, † indicating that this adsorption process is mainly controlled by internal diffusion control. It is also found that K d is decreasing while intercept c is increasing, indicating that the thickness of the boundary gradually increases and the adsorption rate decreases during the adsorption process.…”
Section: Adsorption Kineticsmentioning
confidence: 97%
See 2 more Smart Citations
“…If the intercept (c) in the internal diffusion model is 0, it means that the internal diffusion is the only speed control step. 20 Obviously, it can be seen that c is not zero from Table S2, † indicating that this adsorption process is mainly controlled by internal diffusion control. It is also found that K d is decreasing while intercept c is increasing, indicating that the thickness of the boundary gradually increases and the adsorption rate decreases during the adsorption process.…”
Section: Adsorption Kineticsmentioning
confidence: 97%
“…In order to determine the interaction between the adsorbent and CR molecules, zeta potential analysis was used to investigate the surface charge of the sample particles in aqueous solution. 20 The results of zeta potential analysis are shown in Fig. S5.…”
Section: The Effects Of Mbh and Mba Microspheres On Adsorption Of Difmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Moreover, due to its complex structure, it is very stable to biological degradation and remains in the environment for a long period of time. 18 For removing CR from effluents, different types of adsorbents like activated carbon, 19 shrimp shell powder, 20 mesoporous α-Fe 2 O 3 nanorods, 21 nano-Fe 3 O 4 , 22 kaolin, 23 hydroxyapatite 24 and biogas waste slurry 25 have been used.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Currently, mesoporous a-Fe 2 O 3 with regular morphologies, such as nanoparticles, nanorods, mesoporous lms, mesoporous (hollow) microspheres, and mesoporous walls, have been successfully obtained by chemical and physical routes. [11][12][13] The investigation for mesoporous a-Fe 2 O 3 microspheres revealed that these microspheres with sufficient thickness increase the reactive surface together with many active surface sites, effectually accommodating the volume expansion and enhancing the electronic conductivity. [14][15][16] These favorable structure features of the mesoporous a-Fe 2 O 3 microspheres lead to promising properties for electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%